Growth of Gracilaria manilaensis Yamamoto et Trono (Rhodophyta) under different light intensities, salinities and pH - Mohd Hidayat, Nor Salamah; Mohammad Noor, Normawaty; Mohamad, Mohd Azrul Naim; Abdullah, Najatul Su Ad; Rusly, Siti Amira Sariyathul; Saad, Shahbuddin; Mukai, Yukinori; Darnis, Deny Susanti (Universiti Malaysia Sabah, 2021)
Previous studies have demonstrated that the seaweed, Gracilaria manilaensis, has a high potential of producing agar for the food industry, and is a promising candidate as a dietary supplement for treating cancer and neurological disorders. Unfortunately, not many farms culturing G. manilaensis existed particularly in Malaysia. One of the reasons is limited knowledge of suitable environmental conditions needed for efficient production of the seaweed. Therefore, this study was carriedouttoidentifythebestgrowthconditionsforG.manilaensisunderdifferentlightintensities,salinitiesandpH. To achieve this objective, Gracilaria sp. was collected from a farm and identified based on morphological characteristics before being subjected to three environmental variables simultaneously: light intensities (100 and 1000 lux), salinities (15, 20, 25 and 30 psu) and pH (7.6, 7.8 and 8.0) simultaneously. Specific growth rates were determined for all the treatments. The results showed that G. manilaensis preferred high light intensity (1000 lux), with the growth rate of 1.69 ± 0.08 g/days at the salinity of 15 psu and pH 7.6. No significant differences were found between salinity and growth rate, indicating that G. manilaensis can tolerate a wide range of salinity. The knowledge gained from this study can be used as a guide to increasing the production of G. manilaensis in indoor farming systems. This will ensure sustainable research for G. manilaensis and production